2022
DOI: 10.1021/acsanm.2c01847
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale MXene Interlayer and Substrate Adhesion for Lubrication: A Density Functional Theory Study

Abstract: Understanding the interlayer interaction at the nanoscale in two-dimensional (2D) transition metal carbides and nitrides (MXenes) is important to improve their exfoliation/delamination process and application in (nano)-tribology. The layer–substrate interaction is also essential in (nano)-tribology as effective solid lubricants should be resistant against peeling-off during rubbing. Previous computational studies considered MXenes’ interlayer coupling with oversimplified, homogeneous terminations while neglect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 69 publications
0
27
0
Order By: Relevance
“…It is known that as synthesized MXene surfaces are generally covered by a mixture of randomly distributed surface terminations [ 38 41 ]. Our group has already verified that the chemical behavior of mixed and homogeneous MXene surfaces can be quite different from each other [ 46 ]. To gain a better understanding of MXenes oxidation, we investigated the interaction of water with a Ti 2 CT x layer simultaneously passivated with –F, –O and –OH (in a stoichiometric ratio of about one-third each).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It is known that as synthesized MXene surfaces are generally covered by a mixture of randomly distributed surface terminations [ 38 41 ]. Our group has already verified that the chemical behavior of mixed and homogeneous MXene surfaces can be quite different from each other [ 46 ]. To gain a better understanding of MXenes oxidation, we investigated the interaction of water with a Ti 2 CT x layer simultaneously passivated with –F, –O and –OH (in a stoichiometric ratio of about one-third each).…”
Section: Resultsmentioning
confidence: 99%
“…the preceding noble gas in the periodic table (hence the acronym NG). In a previous work, [ 46 ] we demonstrated that the use of PBE + D NG is more accurate in capturing long-range van der Waals interactions than other dispersion-corrected DFT functionals (e.g. vdW-DF2) when MXenes are involved.…”
Section: Systems and Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…The presence of higher amounts of –F and –O groups on MXenes demonstrates weaker adhesion to ferrous substrates which helps in lubricant deportation under sliding conditions. 375…”
Section: Emerging Materialsmentioning
confidence: 99%